(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The antibacterial activity of extractions from calli cultures of Ajuga genevensis L. was revealed. The character of antibacterial activity and the minimal inhibiting concentration of studied extractions towards E. coli was determined.